PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA DARI PEMBERITAAN MEDIA MASSA DI KOTA PEKANBARU - NATANIKA, YOMI; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Legal protection for children as victims of criminal acts, one of which is avoidance from publication of their identity as regulated in Law Number 11 of 2012 concerning Child Criminal Justice System Article 19 paragraph (1) and (2). But there are still some media / press that publish the identity of the child completely and clearly both in print and electronic media, it can have an adverse impact on the growth and development of children physically, mentally or socially. The purpose of this study was to find out how legal protection for children as victims of criminal acts from mass media coverage in the city of Pekanbaru and how the influence of mass media coverage of children as victims of the crime.This type of research can be classified in the type of sociological juridical research, because in this study the author directly conducts research on the location or place studied in order to provide a complete and clear picture of the problem under study.This research was conducted in the city of Pekanbaru. while the population and sample are all parties related to the problem under study in this study, the data sources used are primary data, secondary data and tertiary data and data collection techniques in this study observation, interviews and literature review.Legal protection for children as victims of criminal acts whose identity is published is the recovery of good name for the child must also be done so that later the child does not feel afraid when dealing with the surrounding community. The results of this research can be interpreted as any legal protection efforts against freedom and rights child rights and various interests related to child welfare. Legal sanctions are accepted by anyone who violates the obligations as referred to in Article 19 paragraph (1) shall be punished with a maximum imprisonment of 5 (five) years and a maximum fine of Rp. 500,000,000.00 (five hundred million rupiahs). Suggestions in this thesis research, it is hoped that media / press journalists will better understand the applicable legal regulations so that later there will be no more negligence such as publishing the identity of children who are victims of criminal acts.